Soluções baseadas na natureza como elemento integrador entre projetos de drenagem urbana e plano do clima na cidade de São Paulo - Oliveira, Milena de (2023)
The occurrence of intense precipitation, often accelerated by the effects of climate change, is directly associated with episodes of floods, floods and flooding in urban areas. Brazil employs micro and macro drainage systems, mainly using traditional techniques - such as the implementation of current works of art, canalization of streams and rivers, among others - to drain rainwater from cities. A historical analysis of urbanization and the consequences felt by society revealed that such techniques can be complemented by measures to promote resilience in the urban environment, such as sustainable drainage. In this issue, the management of rainwater is addressed, through sustainable drainage, as called Nature-Based Solutions (SbN). The SbN appear as measures that encourage the insertion of green elements in the urban environment, generating benefits beyond flood control, as well as the so-called ecosystem services. The municipality of São Paulo was chosen as the object of study due to the high degree of urbanization and due to recurrent problems with flooding. Based on a documentary analysis of seventeen watershed notebooks prepared by Hydraulic Technological Center Foundation - USP and the Climate Action Plan of the city of São Paulo, strategies for flood control proposed in the city of São Paulo were observed, accelerating SbN in an integrated manner. It was found that the proposals presented in the hydrographic notebooks address, primarily, measures aimed at the construction of Linear Parks to face the serious incidents of drainage problems existing in the city of São Paulo. The research concluded that both analyzed documents dialogue in an integrated way when addressing SbN in urban planning and flood control, however, they propose the aid of SbN practices with various devices, such as green roofs, green walls, urban gardens, biovaletas and permeable pavements in the planning of the strategies of the existing Drainage Notebooks, thus allowing greater integration between the documents and the scope of actions foreseen in PlanClima-SP.